Modeling of narrow and wideband signals scattering by randomly distributed scattering points - Elminowicz, Andrzej; Zajączkowski, Leonard (Archives of Acoustics, 2007)
Presented in the paper issue of surface and volume scattering of acoustic wave in marine environment is fundamental problem related to mono-, bi- and multistatic acoustic systems operating in littoral sea. Reverberation creating as a result of the scattering has a significantly influence on the small target detection. Modeling of narrow and wideband signal scattering has been carried out using MATLAB. To solve the issue we accepted that scattering occurred on randomly distributed points which generated scattering waves received and summed in receiver. Density and arrangement of the points is a measure of environment scattering property. The analyses, by signal processing in matched filter, were made for LFM, HFM and CW signals (for comparison). The effect of signal parameters on scattering was investigated also.